2015
DOI: 10.1186/s12863-015-0283-z
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging local ancestry to detect gene-gene interactions in genome-wide data

Abstract: BackgroundAlthough genome-wide association studies have successfully identified thousands of variants associated to complex traits, these variants only explain a small amount of the entire heritability of the trait. Gene-gene interactions have been proposed as a source to explain a significant percentage of the missing heritability. However, detecting gene-gene interactions has proven to be very difficult due to computational and statistical challenges. The vast number of possible interactions that can be test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…In contrast to the molecular phenotype data, searches for interactions in these phenotypes did not yield any findings passing genome‐wide significance. This is consistent with previous disease studies that have failed to find many replicable interactions in disease studies (Aschard et al., ). In the data here, the lack of any findings may be due to the relatively small sample size or because the effects of the interactions are extremely small (if they exist for covariates correlated with θEUR).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast to the molecular phenotype data, searches for interactions in these phenotypes did not yield any findings passing genome‐wide significance. This is consistent with previous disease studies that have failed to find many replicable interactions in disease studies (Aschard et al., ). In the data here, the lack of any findings may be due to the relatively small sample size or because the effects of the interactions are extremely small (if they exist for covariates correlated with θEUR).…”
Section: Resultssupporting
confidence: 92%
“…a). This is in agreement with recent work showing the limited utility of local ancestry by local ancestry interaction test to identify underlying SNP by SNP interaction when genotype data are available (Aschard et al., ). For the larger effect sizes we simulated, we do see power increasing as the difference between ancestral frequencies increases.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As discussed in our previous work 18 , we expected SNPs in regions of local ancestry-smoking interactions to show multiple-SNP effects on the trait as well as high allelic frequency differentiation at SNPs between ancestral populations. Hence, we performed comparative study of allelic frequencies between the two ancestral populations and fine-mapping analysis to assess the potential presence of multiple causal variants.…”
Section: Follow-up Analysismentioning
confidence: 96%
“…Recently, we found that the correlation between local ancestry and untyped causal variants can be leveraged to detect distant gene-gene interactions in admixed populations through local ancestry-local ancestry screening 18 . That work also demonstrated that the power of such admixture mapping increases with the number of causal variants within local ancestry tested and with the degree of differentiation of variants between the ancestral populations.…”
Section: Introductionmentioning
confidence: 99%